Penerapan Konsep Belajar Kontextual Teaching and Learning (CTL) pada Pelajaran Al-Qur’an Hadits d MTs Asy-Syahadatain Cibeber - Acip, Acip (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
This article discusses the implementation of the Contextual Teaching and Learning (CTL) concept in teaching Al-Qur’an Hadith at MTs Asy-Syahadatain Cibeber. CTL is a learning approach that emphasizes the integration of lesson materials with students' real-life contexts. This study explores the effectiveness of applying CTL in enhancing students' understanding and application of Al-Qur’an Hadith teachings and fostering their interest in learning. The research methods employed include classroom observations, interviews with teachers and students, and analysis of teaching documents. The findings indicate that applying CTL positively impacts students' understanding of Al-Qur’an Hadith materials, as students can relate lessons to everyday life contexts. Implementing CTL enhances students' motivation and interest in the subject. In conclusion, implementing the CTL concept in teaching Al-Qur’an Hadith at MTs Asy Syahadatain Cibeber positively impacts students' understanding, application, and interest in learning. Teachers should continue integrating real-life contexts into teaching to enhance the effectiveness of Al-Qur’an Hadith learning.